"I'm Bart Simpson, who the hell are you?" A study in postmodern identity (re)construction - Ott, Brian L., author; Blackwell Publishing, publisher (Colorado State University. Libraries, 2003)
Difference- and subsequently, identity- is now defined and affirmed through consumer choice. Though generally the author is compelled by the theoretical claims surrounding this apparent shift, in this article he wishes to problematize and then clarify those claims in an important way. Efforts to theorize shifting conceptions of identity have preceded largely without, in Kellner's words, "systematic and sustained examination of the actual texts and practices of popular media culture". Indeed, van Poecke's essay, one of the most sophisticated treatments of this subject, makes not a single reference to a specific media text. Consequently, much of the existing literature regarding postmodern identity represents the break from modernist notions far too cleanly, and in a manner that does not adequately reflect the lived experiences of present-day subjects. The hope is that by studying a specific case, the theory can be refined so as to better assist people in negotiating their rhetorical environments. To accomplish this aim, this article undertakes an analysis of the Fox network's thirty-minute, award-winning animated series, The Simpsons.
I'm Bart Simpson, who the hell are you? A study in postmodern identity (re)construction
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: leisure; media; consumption; identity; difference; modeling identity; Bart; Homer; Lisa